A brief scale for measuring Anti-Intellectualism. (1st August 2017) - Marques, Mathew D.; Elphinstone, Brad; Critchley, Christine R.; Eigenberger, Martin E.
Abstract: This paper describes the development of a brief scale to measure anti-intellectualism, the degree to which one experiences either positive or negative affect while engaged in epistemic activities such as conceptual integration. Using seven samples, the study examined several psychometric components of the measure, including equivalency across community and student/convenience populations, temporal stability, and indications of different forms of validity. The scale was designed to be a brief, reliable and valid measure of individual differences in the degree to which individuals value affect-reinforced need for intellectual engagement. These results suggest that the Anti-Intellectualism Scale may provide a useful tool for the examination of differences in the desire to engage in intellectually challenging activities, and subsequent outcomes such as vocational interest, academic achievement, and democratic citizenship. Highlights: Development of the Intellectualism-Anti-Intellectualism Scale Brief unidimensional scale distinct from intelligence Demonstrated as suitable for use in both student and non-student samples Useful for vocational interest, academic achievement, and democratic citizenship